Perceptions of pre-service elementary teachers toward the use of Artificial Intelligence (AI) in science portfolio creation - Edward Harefa (Privietlab, 2026)
The increasing availability of Artificial Intelligence (AI) tools has begun to influence teaching, learning, and assessment practices in elementary education, including portfolio-based assessment in science learning. This study explores pre-service elementary teachers’ perceptions toward the use of AI in science portfolio creation. Employing a descriptive qualitative research design, data were collected from 15 pre-service elementary teachers through semi-structured interviews and written reflections. The data were analyzed thematically to identify shared perceptions, perceived benefits, and perceived challenges related to AI integration in portfolio-based assessments. The findings revealed that the participants generally held cautiously positive perceptions of AI. They view AI as a supportive tool that can assist students in organizing ideas, improving the clarity of scientific explanations, enhancing visual presentation, and increasing efficiency in portfolio development. However, participants also expressed significant concerns regarding overreliance on AI, reduced critical thinking, authenticity of student work, ethical issues related to authorship and academic honesty, and data privacy. In addition, many participants reported limited preparation and confidence in using AI for instructional and assessment purposes. This study highlights the importance of teacher guidance and clear boundaries to ensure that AI functions as a learning aid rather than as a substitute for student thinking. These findings suggest the need for stronger integration of AI literacy, ethical awareness, and assessment design within teacher education programmes to support the responsible and pedagogically sound use of AI in elementary science education.